2018
DOI: 10.1016/j.lithos.2018.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Mapping magnetic sources at the millimeter to micrometer scale in dunite and serpentinite by high-resolution magnetic microscopy

Abstract: Rock samples can have wide range of magnetic properties depending on composition, amount of ferromagnetic minerals, grain sizes and microstructures. Here, we used scanning magnetic microscopy, a highly sensitive and high-resolution magnetometric technique to map remanent magnetic fields over a planar surface of a rock sample.The technique allows for the investigation of discrete magnetic mineral grains, or magnetic textures and structures with submillimeter scale resolution. Here, we present a case-study of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
(48 reference statements)
1
13
0
1
Order By: Relevance
“…The gradual decrease in susceptibility is interpreted to be due to a range in composition of the Cr‐spinel host and Fe‐rich exsolution microstructures. This interpretation is in agreement with compositional ranges reported by Pastore, McEnroe, ter Maat, et al () on dunite samples from the CS, as well as reported progressive changes in T c in the Fe‐Cr spinel solid solution due to compositional variation in the exsolved phase by Francombe () and Robbins et al (). The T c estimates based on the thermomagnetic curves implies that some exsolution blebs have near‐end‐member magnetite compositions; however, the partially suppressed Verwey transition also indicates a degree of cation substitution or nonstoichiometry.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The gradual decrease in susceptibility is interpreted to be due to a range in composition of the Cr‐spinel host and Fe‐rich exsolution microstructures. This interpretation is in agreement with compositional ranges reported by Pastore, McEnroe, ter Maat, et al () on dunite samples from the CS, as well as reported progressive changes in T c in the Fe‐Cr spinel solid solution due to compositional variation in the exsolved phase by Francombe () and Robbins et al (). The T c estimates based on the thermomagnetic curves implies that some exsolution blebs have near‐end‐member magnetite compositions; however, the partially suppressed Verwey transition also indicates a degree of cation substitution or nonstoichiometry.…”
Section: Discussionsupporting
confidence: 92%
“…The chemical composition of the exsolution microstructures and host chrome‐spinel in CS rocks is reported by Pastore, McEnroe, ter Maat, et al (). The composition is obtained by electron microprobe analysis and is [(Fe 2+ 0.94 Mg 0.07 Ni 0.01 ) 1.02 (Fe 3+ 1.33 Cr 0.46 Al 0.15 Ti 0.03 ) 1.97 O 4 ] for the exsolution microstructures and [(Fe 2+ 0.76 Mg 0.25 ) 1.01 (Fe 3+ 0.46 Cr 0.74 Al 0.75 Ti 0.03 ) 1.97 O 4 ] for the host chrome‐spinel.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…These anomalies reflect the small‐scale variations of the magnetization, which commonly can record geologically meaningful information. Numerous studies have used the information derived from the fine scale magnetization for applications in the fields of paleomagnetism (e.g., Fu et al, ; Oda et al, ; Weiss et al, , ; Weiss et al, ), environmental magnetism (Noguchi et al, ), and rock magnetism (Church & McEnroe, ; de Groot et al, ; Egli & Heller, ; Hankard et al, ; Lima et al, ; Nakamura et al, ; Pastore et al, ; Schmidt et al, ; Tominaga et al, ; Weiss et al, ).…”
Section: Introductionmentioning
confidence: 99%